A basic epistemic logic and its algebraic model - Hércules de Araujo Feitosa; Mariana Matulovic; Ana Claudia de J. Golzio (Intermaths, 2023)
In this paper we propose an algebraic model for a modal epistemic logic. Although it is known the existence of algebraic models for modal logics, considering that there are so many different modal logics, so it is not usual to give an algebraic model for each such system. The basic epistemic logic used in the paper is bimodal and we can show that the epistemic algebra introduced in the paper is an adequate model for it.